Antioxidant and antiplatelet potential of different methanol fractions and flavonols extracted from onion (Allium cepa L.) - Ko, Eun Young; Nile, Shivraj Hariram; Jung, Yi Sook; Keum, Young Soo (3 Biotech, 2018)
In this study, we reported the potential of various methanol fractions of onion (MFO) and its components quercetin and quercetin glucosides on platelet aggregation and antioxidant activity. The onion extracts were separated into several fractions using methanol and water. Further, these extracts were analyzed using simple high-performance liquid chromatography–diode array detector method to separate quercetin (Q), quercetin-4′-O-monoglucoside and quercetin-3, 4′-O-diglucoside from onion sample. It was observed that the bioactive compounds were accumulated in the non-polar portions rather than in the polar one. MFO and flavonol glucosides inhibited collagen-induced platelet aggregation, and the anti-aggregatory effects were comparatively studied using rat PRP (platelet-rich plasma). Among the extracted compounds, quercetin was found as a potent inhibitor of platelet aggregation compared to quercetin glucosides, whereas quercetin glucosides showed high antioxidant activities. These results suggest that MFO, quercetin and quercetin glucosides have powerful antiplatelet and antioxidant activities. These studies provide possible information leading to the intake of onions rich in these flavonols as a dietary supplement and functional food ingredient to prevent thrombosis and cardiovascular and oxidative stress-related diseases and might be utilized as a real source of valuable phytochemicals for the pharmaceutical and food industries for the development of antioxidant, anticoagulant and antiplatelet agents.
Keywords: Antioxidant; Antiplatelet; HPLC; Onion; Quercetin; Quercetin glucosides